ChemInform Abstract: Enantioselective β‐Boration of Acyclic Enones by a [2.2]Paracyclophane‐Based N‐Heterocyclic Carbene Copper(I) Catalyst. Issue 28 (21st June 2013) - Zhao, Lei; Ma, Yudao; He, Fuyan; Duan, Wenzeng; Chen, Jianqiang; Song, Chun
Abstract The new planar and centrally chiral triazolium salt (NHC) efficiently promotes the asymmetric conjugate boration of acyclic enones yielding synthetically important organo‐boron compounds with excellent enantioselectivity in short times.